The Effect of Camel Milk &Urine in Viability of Entamoeba histolytica Growing in Culture Media LEM - Al-aboody, Basad Aqrab; Faris, Huda N.; Al hassany, WafaÂ´a Hassan (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
This study included the isolation of the parasite Entamoeba histolytica from bloody mucoid diarrhea specimens of patients suffering from amoebic dysentery and cultivation of parasite in Locke-egg medium (LEM) to study  the effect of camel's milk and urine on the viability of E . histolytica with different concentrations (1 , 5  and 10 % ). The ability of camel's milk and urine in inhibiting the E . histolytica viability  is examined after  24 and 48 h of incubation The results showed that the activity of camel's milk and urine was  directly proportional  with  the increase  in concentration and incubation period. Since the  highest rate of parasite death reached ( 99.5% and 99.4% ) in 10% milk and urine respectively after 48 h of incubation while the rate of parasite death was reached after 24 h of incubation and to the same concentration ( 94.2% and 96.2% ) of milk and urine respectively,   control group was (4.2% and 6.5% ) after 24 and 48 h of incubation respectively.